2019
DOI: 10.1021/acscatal.9b00010
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Cu/CeO2-x Nanocrystalline Heterodimers with Interfacial Active Sites To Promote CO2 Electroreduction

Abstract: Synergistic effects at metal/metal oxide interfaces often give rise to highly active and selective catalytic motifs. So far, such interactions have been rarely explored to enhance the selectivity in the electrochemical CO 2 reduction reaction (CO 2 RR). Herein, Cu/CeO 2-x heterodimers (HDs) are synthesized and presented as one of the prime examples where such effects promote CO 2 RR. A colloidal seeded-growth synthesis is developed to connect the two highly mismatched domains (Cu and CeO 2-x) through an interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
156
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(171 citation statements)
references
References 54 publications
4
156
0
Order By: Relevance
“…bimetallics and alloys) represents an additional degree of freedom that can contribute greatly to the CO 2 RR, as already demonstrated in many contributions. 34,[36][37][38][39][40][41][42][43] Finally, functionalized NCs can be integrated into more technologically relevant gas-diffusion electrodes in the future. 44 The electrocatalytic testing of the hybrid catalysts revealed that all of the ligands promote CO 2 RR over HER compared to the as-synthesized AgNCs, and interesting effects of the anchoring and tail groups on the tuning of the activity and selectivity have been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…bimetallics and alloys) represents an additional degree of freedom that can contribute greatly to the CO 2 RR, as already demonstrated in many contributions. 34,[36][37][38][39][40][41][42][43] Finally, functionalized NCs can be integrated into more technologically relevant gas-diffusion electrodes in the future. 44 The electrocatalytic testing of the hybrid catalysts revealed that all of the ligands promote CO 2 RR over HER compared to the as-synthesized AgNCs, and interesting effects of the anchoring and tail groups on the tuning of the activity and selectivity have been discovered.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, colloidal chemistry has proven to be one of the most suitable synthetic methods to achieve tunability on hybrid materials at the nanoscale. [1][2][3][4][5][6][7][8][9][10] Indeed, colloidal hybrid nanocrystals (HNCs) have been utilized as the key components in a variety of applications spanning from catalysis to plasmonics to biomedicine and energy conversion. [1][2][3][4][5][6][7][8][9][10] Phase segregation, partial cation exchange, thermally induced coalescence and seeded growth are some of the strategies employed to access a huge library of HNCs.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] Indeed, colloidal hybrid nanocrystals (HNCs) have been utilized as the key components in a variety of applications spanning from catalysis to plasmonics to biomedicine and energy conversion. [1][2][3][4][5][6][7][8][9][10] Phase segregation, partial cation exchange, thermally induced coalescence and seeded growth are some of the strategies employed to access a huge library of HNCs. [1][2][3][4][5][6][7][8][9][10] Despite the beautiful examples reported in the literature, some material combinations remain more challenging or underexplored than others.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations